TUTURAN ILOKUSI BAHASA MOTIVASI MARIO TEGUH PADA JEJARING SOSIAL FACEBOOK - Amanah Hijriah; Wahyu Damayanti (tuahtalino, 2016)
This study analyzes the motivational speech language illocutionary Mario on social network facebook . The purpose of this study to describe the type speech illocutionary language Mario on social network facebook . The method in this research is descriptive . Data sourced from social networks facebook fun page in the form Mario in the period January 2016 Mechanical analasis data used in this study is a decisive element pilah techniques and pragmatic techniques in a unified method . The results of this study suggest that the type speech illocutionary used Mario on social networking facebook month period in January 2016 , including assertive , directive , commissive , expressive and declarative . Type speech illocutionary directive more assertive and dominant.